2016
DOI: 10.4081/ejh.2016.2710
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor expression in human fascial tissue

Abstract: Many epidemiologic, clinical, and experimental findings point to sex differences in myofascial pain in view of the fact that adult women tend to have more myofascial problems with respect to men. It is possible that one of the stimuli to sensitization of fascial nociceptors could come from hormonal factors such as estrogen and relaxin, that are involved in extracellular matrix and collagen remodeling and thus contribute to functions of myofascial tissue. Immunohistochemical and molecular investigations (real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Although in literature it is demonstrated that the fibroblasts replication in culture does not correlate with donor age [43], we expect differences in responsiveness depending on the age and period of the patients as we have demonstrated in our previous work, in which the expression of the receptors for estrogen and for relaxin-1 resulted lower in post-menopausal women, according to the decrease in estrogen hormone levels [3]. Although in the next future this work will be deepened by repeating the analyzes on other cells isolated from premenopausal women and then comparing the results with samples of post-menopausal women, we have chosen for this pilot in vitro study the cells that in our previous work had shown a homogeneous and high positivity of expression for hormone receptors [3]. Furthermore we analysed only two hormones (β-estradiol and relaxin-1), with no reference to the extracellular assembly and to the degradation of the collagen fibers, essential to determine the organization of the ECM and consequently the stiffness of a tissue [44].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although in literature it is demonstrated that the fibroblasts replication in culture does not correlate with donor age [43], we expect differences in responsiveness depending on the age and period of the patients as we have demonstrated in our previous work, in which the expression of the receptors for estrogen and for relaxin-1 resulted lower in post-menopausal women, according to the decrease in estrogen hormone levels [3]. Although in the next future this work will be deepened by repeating the analyzes on other cells isolated from premenopausal women and then comparing the results with samples of post-menopausal women, we have chosen for this pilot in vitro study the cells that in our previous work had shown a homogeneous and high positivity of expression for hormone receptors [3]. Furthermore we analysed only two hormones (β-estradiol and relaxin-1), with no reference to the extracellular assembly and to the degradation of the collagen fibers, essential to determine the organization of the ECM and consequently the stiffness of a tissue [44].…”
Section: Discussionmentioning
confidence: 96%
“…Estrogens have long been known as a regulating factor of metabolism in tissues such as bone, muscle, cartilage, tendon and ligament, affecting the musculoskeletal functions [1]. The estrogen-beta receptor has also been described recently in the tissue of tendons and ligaments [2], and only in one of our recent works [3] the expression of sex hormone receptors was also demonstrated in the muscular fasciae. It was recently observed that knee laxity is significantly greater around ovulation, when estrogen peaks [4], with an increased risk of injury [5].…”
Section: Introductionmentioning
confidence: 99%
“…We know that the fascial tissue is in close proximity to the muscles (deep fascia and epimysium) and that it can suffer from the same non-physiologic adaptation of the contractile districts (and vice versa). 28 , 50 , 52 We know that the nociceptors that are in the fascia have a lower threshold of activation if the fascial tissue is less compliant (greater stiffness). 52 We can suppose that the deep fascia covering externally the ribs is one of the causes of thoracic pain.…”
Section: Thoracic Pain: Possible Fascial Somatic Causesmentioning
confidence: 99%
“…Fasciae have recently become a topic for discussion and the subject of an increasing number of publications (Condino et al, 2015;Fede et al, 2016;Petrofsky and Lee, 2015;Stecco et al, 2019). International conferences and courses have been dedicated to them (International Fascia Research Congress and others listed by Fascia Research Society).…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones appear to have significant effects in women (Russek, 1999), the key hormones being estrogen, *Correspondence to: Zuzana Sedlackova, Departments and faculties of Medicine and Dentistry, University Hospital Olomouc, Palacky University Olomouc, I. P. Pavlova 6, 775 20 Olomouc, Czech Republic. E-mail: zuzana.sedlackova@fnol.cz progesterone, and relaxin (Dragoo et al, 2011;Fede et al, 2016). We found two reviews of the influence of the menstrual cycle, especially of estrogen levels, and of hormonal contraceptive use on ligament laxity (Belanger et al, 2013;Herzberg et al, 2017); however, both reported inconsistency in the results and focused on the anterior cruciate ligament (ACL).…”
Section: Introductionmentioning
confidence: 99%